Ensaio de operacionalização de Indicadores de Desenvolvimento Sustentável por modelação geográfica - Morgado, Paulo (Finisterra, 2003)
PRACTICE OF SUSTAINABLE DEVELOPMENT INDICATORS BY GEOGRAPHIC MODELING. This article presents a proposal of how to put in practice the concept of sustainable development - that as been strictly seeing in a theoretical point of view, as well a tribune speech and with very imprecise conceptual boundaries – supported by the use of Geographic Information System (GIS). The exercise mentioned here it’s only the technical part of a more extensive project, it could be resume in three steps: 1) research – definition and enlightening of sustainable development concept, indicators definition, determination of theorist and methodological frame. 2) practice – identification and acquisition of important information, editing and validating information, creating a GIS project, definition and construction of sustainable development indicators, adaptation and conception of geographic model. 3) Analysis – collect and interpretation of geographic model results by confronting it to some theories claimed by important researchers. For the exercise setting up, as well to develop the conceptual methodology of casual model, GIS as been a fundamental instrument to acquire, integrate, manipulate, manage and visualize geographic information